Diagnostic accuracy of biopsied skin lesions in dermatology and plastic surgery clinics - (:unkn) unknown (My University, 2007)
Considering the increasing frequency of malignant skin lesions in the last decades, appropriate diagnosis of all kinds of skin lesions has become more important than ever. This study compares the type of skin lesions, seen and treated by dermatology and plastic surgery clinics in Marmara University Hospital, the preferred method of diagnosis, and the correlation between the clinical and pathological diagnosis for each clinic. Patient records, for the years 2000 and 2001, were reviewed retrospectively from the archives of the pathology department. Specimens, 495, from the dermatology clinic and 285 specimens from the plastic surgery clinic were reviewed. In the plastic surgery clinic, excisional biopsy was by far the most utilized method (93.7%). In the dermatology clinic, punch biopsy was the most frequently used method (47.9%). In 317 of the 495 dermatology specimens (64%) and in 175 of the 285 plastic surgery specimens (61.4%), the clinical diagnosis correlated with the pathological diagnosis. Statistical comparison of the overall correct diagnosis ratio between the two clinics did not show a significant difference (p >0.05). Patient spectrums of the two clinics were different. Benign and malignant neoplastic proliferations were predominant in the patient spectrum of the plastic surgery clinic. Inflammatory and infectious and benign neoplastic proliferations were predominant in the patient spectrum of the dermatology clinic. Biopsy methods preferred were also different, but accuracy in clinical diagnosis was comparable. © Springer-Verlag 2007.
Keywords: Dermatology; Diagnostic accuracy; Plastic surgery; Skin lesions